Parameters of Apoptosis and Proliferative Activity in the Stomach in Patients with Rheumatological Diseases - Marufkhanov Khamid Makhmudovich; Sibirkina Marina Valerievna; Eshmurzaeva Aida Abduganiyevna (Genius Journals, 2023)
Programmed cell death (PCD) is one of the key links in the pathogenesis of gastritis and peptic ulcer disease. In the course of the study, the proliferative-apoptotic status of epithelial cells of the gastric mucosa was determined in rheumatological patients at the onset of the disease and during treatment with NSAIDs in comparison with peptic ulcer, which allows us to conclude that reparative processes are reduced.
Keywords: apoptosis; proliferation; epithelial cells of the gastric mucosa